2021
DOI: 10.37905/tjas.v2i1.10478
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and the appearance of new whale sharks (Rhincodon typus) as a unique phenomenon in the Kwatisore waters within the Cenderawasih Bay National Park area, Papua

Abstract: Research on whale sharks (Rhincodon typus) was conducted from September 1st to December 20th, 2020 in Kwatisore waters. Kwatisore waters are within the conservation area of the Cenderawasih Bay National Park and have specifications for the number of whale sharks and the appearance of new individuals. The appearance of whale sharks individuals takes place every day around the boat life net area that is anchored in Kwatisore waters. This study aims to assess whale shark aggregation, particularly the total appear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…The phenomenon that can be seen is during the nike fish season. Maruanaya, et al (2022) reported that the number of individuals appearing in Kwatisore waters is closely related to the catch of anchovies by Bagan fishermen.…”
Section: Discussionmentioning
confidence: 99%
“…The phenomenon that can be seen is during the nike fish season. Maruanaya, et al (2022) reported that the number of individuals appearing in Kwatisore waters is closely related to the catch of anchovies by Bagan fishermen.…”
Section: Discussionmentioning
confidence: 99%
“…The appearance of whale sharks in Kwatisore waters occurs every day and is not dependent on the season [8]. The concentration of whale sharks' appearance is near the Bagan area, where it is closely related to the capture and feeding of anchovies by the fishermen [16]. Whale sharks are attracted by the concentrations of pelagic fish and consume anchovies (Engraulis australis) near the area of Whale Island, in the Plenty Bay New Zealand [13,14].…”
Section: The Phenomenon Of Whale Shark Appearance In Kwatisore Watersmentioning
confidence: 99%
“…Kwatisore waters is the only area for anchovy fishing which can be carried out at any time in the lift net boat. The stocks availability of natural anchovy in Kwatiosre waters is the main food for whale sharks thus it makes Kwatisore waters a key foraging site [16]. The increasing frequency of whale shark appearances in Kwatisore waters is correlated with the increasing in anchovy catches while one of the factors that causes the lack of intensity of whale shark appearances on the surface is the reduced numbers of anchovy in Kwatisore waters [7,11].…”
Section: The Phenomenon Of Whale Shark Appearance In Kwatisore Watersmentioning
confidence: 99%
See 2 more Smart Citations